„A Kúria méltósága”: Gondolatok Szemák Jenő portréjának visszahelyezéséről - Tímár, Balázs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
In the hallway of the Hungarian Supreme Court’s temporary building there are portraits of the previous presidents of the Court. For decades, Jenő Szemák’s portrait was absent due to his role during the end of World War II and mostly because of the fact that he was a prominent figure in the Arrow Cross Regime. By this year his portrait was hung there with additional notes. This action brought up the question of Szemák’s actual role and the determination of the Arrow Cross Movement. The main question is the independence and relevance of the Supreme Court during the darkest months of Hungary’s history. Between 1918 and 1945 two radical course took power in Hungary thus the article brings up comparisons of them since their point of view of the courts was different.